Makna di balik Qur’an surah Al-Baqarah ayat 58: Pengajaran dari perintah Allah kepada Bani Israil - Faizeh, Faizeh (Maliki Interdisciplinary Journal, 2024)
Surah Al-Baqarah verse 58 in the Qur’an provides profound teachings about obedience and human responsibility to Allah’s commands. This verse narrates Allah’s command to the Children of Israel to enter a city humbly and say "hithah" as a plea for forgiveness. The teachings from this verse emphasize the importance of obedience, humility, and collective responsibility in maintaining morality and social ethics. Through the analysis of this verse, we understand that forgiveness and humility are keys to receiving blessings from Allah, while disobedience and arrogance lead to punishment. This verse also encourages introspection and self-reflection, urging Muslims to improve themselves and enhance the quality of their worship. Thus, Surah Al-Baqarah verse 58 is not only relevant in a historical context but also serves as a practical and dynamic guide for life throughout the ages.